EXTERNAL PARTY RECOGNITION ON ESG DISCLOSURE TO STOCK PRICE: A CASE STUDY OF ESG DISCLOSURE AWARDS IN INDONESIAN STOCK EXCHANGE - Dwi Octavia; Helen Jayanti; Jayson Gautama Lee; Richard Arlie; Lindrianasari (Bina Nusantara University, 2023)
This research aims to find further empirical evidence of the connection of environmental disclosure with share price. We took into consideration potential investor doubt on company ESG disclosure. This research aims to find further empirical evidence of the connection of environmental disclosure with the share price. We considered potential investor doubt on company ESG disclosure because of potentially biased reporting from management predicted by agency theory and attempted to study the effects when this doubt is removed by external recognition of the company's ESG disclosures. Abnormal returns of companies are tracked using daily closing price data from Bloomberg, and further testing is done using the binomial distribution. Our study has found that companies that obtain external recognition experience an increase in abnormal returns after the award announcement date. This finding implies that external parties' recognition of the company's environmental performance will obtain positive market sentiment and is indicated by increased stock returns.